THE INTERCULTURAL STRUGGLE: PMM STUDENTS' PERSPECTIVES ON CULTURE SHOCK AT UNIVERSITAS NEGERI MAKASSAR - Amrina, Muthiah; Halim, Abd; Sunra, La (Institut Agama Islam Negeri (IAIN) Bone, 2025)
This qualitative study explores the determinants of culture shock experienced by students participating in the Program Merdeka Mengajar (PMM) at Universitas Negeri Makassar (UNM). Using Orlay’s (2021) framework on cultural adaptation, the research investigates the challenges faced by 5 PMM students as they navigate their academic and social environments in a new cultural setting. Through in-depth interviews, the study identifies key factors contributing to culture shock, including language barriers, differences in teaching methodologies, and habit. Findings suggest that these factors significantly impact students' academic performance, mental well-being, and overall adjustment to university life. The study highlights the need for targeted support mechanisms, such as cultural orientation programs and peer mentoring, to mitigate the negative effects of culture shock and promote smoother transitions for future PMM participants. This research contributes to the understanding of cross-cultural challenges in higher education and provides insights for improving the PMM experience at UNM.